An empirical investigation of factors influencing user satisfaction with online services of mobile communication providers: study of Kuwait - Alzabi, Tami; Shah, Asadullah (Kaerntner Botanikzentrum, Klagenfurt, Austria, 2015)
Mobile communication penetration is high in many countries particularly Kuwait, the mobile communication providers in Kuwait offer many online services and the competition among them is very high. They seek user satisfaction in order to sustain their customers and attract new ones. This study proposed multidimensional user satisfaction model to identify the factors that impact user satisfaction of online services. This study found that information quality, system quality, and service quality have significant impact on user satisfaction with online service in Kuwait.